Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
log/ln probelm?
2lnx-(lnx)^2=0
Can someone explain how to do this problem
5 Answers
- llafferLv 74 years ago
You have:
2 ln(x) - [ln(x)]² = 0
We can factor out an ln(x) to create the product of two values that are equal to zero, so one of them must be equal to zero:
ln(x) [2 - [ln(x)] = 0
So now we have:
ln(x) = 0 and 2 - ln(x) = 0
x = 1 and ln(x) = 2
x = 1 and e²
- 4 years ago
Let ln(x) = t
2t - t^2 = 0
t^2 - 2t = 0
t * (t - 2) = 0
t = 0 , 2
ln(x) = 0 , 2
x = e^0 , e^2
x = 1 , e^2
- How do you think about the answers? You can sign in to vote the answer.